Disease prevention and control along the Thai-Myanmar border by local administrative organizations - ชมภูนุช, จุฑาทิพย์; ชมภูนุช, นิพภยา; อติรัตนา, ขนิษฐา (Disease Control Journal, 2013)
This Study aimed to assess the knowledge and the role of the personnel in the local authority organi¬zations (LAO) on disease prevention and control at borders. Data were collected from 34 LAOs in Kanchanaburi, Ratchaburi, Petchaburi and Prachuapkhirikhan Provinces. The results revealed that majority (85.90#0 of LAOs were faced with endemic diseases such as malaria and dengue fever, upto 88.2 % and 91.2°/o of LAOs had policy on health and disease prevention and control, respectively. Most health projects were created by coordination of the LAOs and the health officers (58.8%). Over 80°/o of LAOs had knowledge on disease prevention and control although only 76.5% had the knowledge on "Encourage of community to find health problems for prevention and control". Major roles of the LAOs were annual budget allocation and cooperation with public health agencies in the sub-districts, while the role on gathering information on cross-borders labors was limited. The limitations of LAOs were inadequate personnel (26.5%) and the lack of knowledge on the endemic diseases in their settings (8.8%).